Spatially fractionated radiation therapy for treating recurrent glioblastoma: a dosimetric feasibility study - Zhou, Yuwei; Tanny, Sean; Milano, Michael T.; Marples, Brian; Li, Fiona; Jung, Hyunuk; Webster, Matthew; Podgorsak, Alexander R.; Yoon, Jihyung; Rivais, Wesley; Hazoglou, Michael J.; Zheng, Dandan (Frontiers in Oncology, 2026)
ObjectiveSpatially fractionated radiation therapy (SFRT) shows promise for treating bulky, advanced, or recurrent tumors. To evaluate the feasibility of SFRT for patients with recurrent glioblastoma (GBM), we conducted a planning study involving 14 patients, analyzing vertex target volume (VTV) contours and cumulative doses to both targets and organs at risk (OARs).MethodThe patients were divided into two groups based on gross tumor volume (GTV): 10 patients with GTV > 15 cc; 4 patients with GTV ≤ 15 cc. SFRT was planned as an upfront boost, using LATTICE radiotherapy (LRT) and stereotactic central ablative radiation therapy (SCART) respectively. With a LRT technique, vertex diameters ranged from 0.8–1.5 cm, with center-to-center spacing of 2–4 cm.ResultGTV geometry—not size—determined mean vertex diameter (MVD: 0.99 ± 0.12 cm), spacing (2.93 ± 0.34 cm), and the VTV-to-GTV ratio (VGR: 6.6 ± 1.7%). With a SCART technique, the mean VGR was 25.8 ± 10.0%. Compared with the original sum plan, the cumulative EQD22 dose in the SFRT sum plan to critical OARs was well-controlled, such as the brainstem with a difference of 0.36 ± 1.00%. However, V120Gy to the brain in the SFRT sum plan increased by 4.51 ± 3.97 cc, for the 12 patients with an original V120Gy < 2 cc. Increased V120Gy to the brain might elevate the risk of radiation-induced necrosis.ConclusionIn summary, our planning study demonstrates that dosimetrically acceptable SFRT plans can be achieved for recurrent GBM. The main clinical consideration is balancing the potential benefit of SFRT against the risk of radiation-induced necrosis.